U-shaped association between triglyceride-glucose index and acute kidney injury in critically ill children with cardiac diseases - Du, Jiaxing; Ma, Keze; Ye, Zhiwei; Song, Juanli; Chen, Sujun; Xiong, Zhenlin; Zheng, Weinan; Li, Meifei; Yu, Huiyi; Zhang, Fen (Frontiers in Endocrinology, 2025)
BackgroundThe triglyceride–glucose (TyG) index, a surrogate of insulin resistance (IR), has been linked to acute kidney injury (AKI) in adults, but its relevance in critically ill children with cardiac disease is unclear. This study aimed to examine this relationship in this vulnerable population.MethodsThis retrospective analysis drew on data from the Pediatric Intensive Care (PIC) database, comprising 2298 critically ill children treated in the Cardiac Intensive Care Unit (CICU) between 2010 and 2019. The primary outcome was the AKI incidence, whereas secondary outcome focused on the occurrence of severe AKI. Restricted cubic splines (RCS) assessed nonlinearity. Multivariate two-segment Cox regression analyses estimated hazard ratios (HRs) across TyG segments after adjustment for confounders. Subgroup analyses evaluated effect modification across clinical strata.ResultsAmong 2,298 CICU pediatric patients (48.7% male), 15.6% developed AKI. A U-shaped relationship between the TyG index and AKI was identified using RCS. Specifically, When the TyG index was below 8.602, an inverse relationship was observed with the primary outcome (HR 0.69, 95% CI 0.48–0.98). Conversely, values at or above 8.602 were positively associated with the AKI incidence (HR 1.63, 95% CI 1.15–2.31). Similarly, for the secondary outcome, the inflection was at TyG 8.757: <8.757, HR 0.53 (0.28–0.99); ≥8.757, HR 2.75 (1.18–6.42). Subgroup and sensitivity analyses reinforced the robustness of these findings.ConclusionsThe TyG index showed a nonlinear, U-shaped association with AKI in critically ill children with cardiac disease, with inflection points around 8.602 (AKI) and 8.757 (severe AKI). These findings suggest that TyG may support bedside risk stratification in this population.